The effect of a neuromuscular warm-up on physical performance in youth field hockey players with two footwear conditions - Schlewing, J. (Stellenbosch University, 2022)
The FIFA 11+ warm-up program has consistently been shown to decrease injury rates, reduce injury risk factors, and enhance performance in various youth club sport populations, with bias towards football. Limited research addresses the 11+ as a suitable program for other field-based team sports and whether the program can be successfully implemented in a school sport environment. The first aim of this study was to assess the influence of the FIFA 11+ warm-up program on various physical performance measurement in female youth field hockey players. The second aim was to assess whether adaptations differ when performing the intervention barefoot as compared to shod. Field hockey players (n = 40; 16.2 } 1.23 years) from three teams from a South African high school were recruited and randomly assigned to either a barefoot or shod intervention group. A testing battery consisting of five physical performance tests, namely Y-Balance, Single-leg hop, Counter-movement Jump, Sprint, and Illinois Agility, was conducted before and after a nine-week intervention utilizing the 11+ twice a week, 20 min per session. Mixed model ANOVAfs were conductd with the full data set of 34 participant with the participants as random effect (to account for repeated measurements), and intervention, time, limb side as fixed effects. Both groups significantly improved (p <0.05) their performance pre- to post intervention in all tests. No statistically significant differences (p >0.05) were found between the two groups with mostly small effect sizes (ES . 0.2). The FIFA 11+ is a suitable program for female youth field hockey players in a school sport environment to contribute to the development of physical performance and decrease injury risk factors. Performing the warm-up program barefoot or shod appeared to be equally effective to improve physical performance in this population.